2017
DOI: 10.1093/infdis/jix534
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Proteomic Analysis of Serum After Akhmeta Virus Infection: New Suspect Case Identification and Insights Into Poxvirus Humoral Immunity

Abstract: Serologic cross-reactivity, a hallmark of orthopoxvirus (OPXV) infection, makes species-specific diagnosis of infection difficult. In this study, we used a variola virus proteome microarray to characterize and differentiate antibody responses to nonvaccinia OPXV infections from smallpox vaccination. The profile of 2 case patients infected with newly discovered OPXV, Akhmeta virus, exhibited antibody responses of greater intensity and broader recognition of viral proteins and includes the B21/22 family glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, the low incidence of MPXV infection, low human-to-human transmission, and the observation that MPX is an acute rather than persistent infection makes superinfection or co-infection with VARV unlikely. While these speculations cannot be examined experimentally due to ethical consideration and dual use risk [201], analysis of historical/retrospective samples by using next generation sequencing and proteomic technologies [202,203] will shed light on the role of co-infection/superinfection, recombination and preexisting MPXV antibodies to VARV and MPXV infection biology. These studies are essential to our understanding of the host and viral factors that modulate MPXV pathogenesis and its possible emergence as a VARV-like pathogen.…”
Section: Co-infection and Recombinationmentioning
confidence: 99%
“…However, the low incidence of MPXV infection, low human-to-human transmission, and the observation that MPX is an acute rather than persistent infection makes superinfection or co-infection with VARV unlikely. While these speculations cannot be examined experimentally due to ethical consideration and dual use risk [201], analysis of historical/retrospective samples by using next generation sequencing and proteomic technologies [202,203] will shed light on the role of co-infection/superinfection, recombination and preexisting MPXV antibodies to VARV and MPXV infection biology. These studies are essential to our understanding of the host and viral factors that modulate MPXV pathogenesis and its possible emergence as a VARV-like pathogen.…”
Section: Co-infection and Recombinationmentioning
confidence: 99%
“…To limit transmission during the 2022 MPXV outbreak, public health agencies recommend Smallpox vaccination, as previous studies have shown protection from MPOX disease using the Smallpox vaccines such as IMVANEX or ACAM2000 [27][28][29][30][31] . The immunology of Dryvax®, ACAM2000 and IMVANEX vaccines has been well studied 27,[32][33][34][35][36] , with antibody responses detected up to 35 years post-Smallpox vaccination 34 . However, studying the immunology to MPXV infection and disease has been limited by the geographical distribution, limited number of human cases worldwide and access to convalescent serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…To limit transmission during the 2022 MPXV outbreak, public health agencies recommend Smallpox vaccination, as previous studies have shown protection from Mpox disease using Smallpox vaccines such as IMVANEX or ACAM2000 27 31 . The immunology of Dryvax®, ACAM2000 and IMVANEX vaccines has been well studied 27 , 32 36 , with antibody responses detected up to 35 years post-Smallpox vaccination 34 . However, studying the immunology to MPXV infection and disease has been limited by the geographical distribution, limited number of human cases worldwide and access to convalescent serum samples.…”
Section: Introductionmentioning
confidence: 99%